Deep Learning Plus Three-Dimensional Printing in the Management of Giant (>15 cm) Sporadic Renal Angiomyolipoma: An Initial Report - Gao, Yunliang; Tang, Yuanyuan; Ren, Da; Cheng, Shunhua; Wang, Yinhuai; Yi, Lu; Peng, Shuang (Frontiers in Oncology, 2021)
Objective: To evaluate the feasibility and effectivity of deep learning (DL) plus three-dimensional (3D) printing in the management of giant sporadic renal angiomyolipoma (RAML). Methods: The medical records of patients with giant (>15 cm) RAML were retrospectively reviewed from January 2011 to December 2020. 3D visualized and printed kidney models were performed by DL algorithms and 3D printing technology, respectively. Patient demographics, intra- and post-operative outcomes were compared between those with 3D-assisted surgery (3D group) or routine ones (control group). Results: Among 372 sporadic RAML patients, 31 with giant ones were eligible for analysis. The median age was 40.6 (18-70) years old and the median tumor size was 18.2 (15-28) cm. 17 of 31 (54.8%) had a surgical kidney removal. Overall, 11 underwent 3D-assisted surgeries and 20 underwent routine ones. A significant higher success rate of partial nephrectomy (PN) was noted in 3D group (72.7% vs 30.0%). Patients in 3D group presented a lower reduction of renal function but experienced a longer operation time, a greater estimated blood loss and a higher postoperative morbidity. Subgroup analysis was conducted between patients undergoing PN with or without 3D assistance. Despite no significant difference, patients with 3D-assisted PN had a slightly larger tumor size and higher nephrectomy score, possibly contributing to a relatively higher rate of complications. However, 3D-assisted PN lead to a shorter warm ischemia time and a lower renal function loss without significant difference. Another subgroup analysis between patients under 3D-assisted PN or 3D-assisted RN showed no statistically significant difference. But the nearness of tumor to the second branch of renal artery was relatively shorter in 3D-assisted PN subgroup than that in 3D-assisted RN subgroup and the difference between them was close to significant. Conclusions: 3D visualized and printed kidney models appear to be an additional tool to assist operational management and avoid a high rate of kidney removal for giant sporadic RAMLs.